2020
DOI: 10.3390/ijerph17145113
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Problem of Access to Public Health Insurance Schemes among Cross-Border Migrants in Thailand through Systems Thinking

Abstract: Thailand has become a popular destination for international migrant workers, particularly from Cambodia, Lao PDR, and Myanmar. However, only a fraction of these migrant workers were insured by public health insurance. The objective of this study was to apply systems thinking to explore contextual factors affecting access to public health insurance among cross-border migrants in Thailand. A group model building approach was applied. Participants (n = 20) were encouraged to share ideas about underlying drivers a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Pregnant women with low wealth status probably do not have a fixed source of income. A pregnant woman or her husband has a type of job that is not permanent, making it difficult to set aside income to pay health insurance premiums [18,20,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women with low wealth status probably do not have a fixed source of income. A pregnant woman or her husband has a type of job that is not permanent, making it difficult to set aside income to pay health insurance premiums [18,20,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The Social Security Act 2015 [ 17 ] indicates that employers must have their wage deducted in the same proportion of migrants as part of payroll contribution. However, a qualitative study by Kunpeuk et al, pointed out that some employers elude the law by not contributing to payroll tax, and this meant that their migrant workers were uninsured [ 18 ]. Aside from this breach of law by employers, paying for health insurance premiums was avoided by some migrant employees, especially those in good health who found that insurance provided little benefit compared with their health needs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a qualitative study by Kunpeuk et al, pointed out that some employers elude the law by not contributing to payroll tax, and this meant that their migrant workers were uninsured [ 18 ]. Aside from this breach of law by employers, paying for health insurance premiums was avoided by some migrant employees, especially those in good health who found that insurance provided little benefit compared with their health needs [ 18 ]. This situation was also found in China where uninsured migrants expressed that they did not want to join a health insurance plan because paying for health services by out-of-pocket was a better approach economically than making regular payments [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both MOU and OSS migrants need to pass a health screening for serious communicable diseases, such as tuberculosis, filariasis, and elephantitis, before being issued a work permit [ 19 ]. The majority of MOU migrants undertake the health check in Thailand in private hospitals (with certified standards as approved by the Hospital Accreditation System, or the Joint Commission International or International Standardization Organisation) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that Thailand shares a very long border with its neighbouring countries, the influx of undocumented migrants still continues [ 3 ]. Although the government attempts to address this problem by various means (including the OSS and the MOU), it seems that the nationality verification (NV) process still faces many challenges, and the volume of undocumented migrants is believed to be underestimated [ 20 ]. Since 2020, COVID-19 and its impact have put pressure on the global economy.…”
Section: Introductionmentioning
confidence: 99%